2023
DOI: 10.1590/1981-6723.00622
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical composition and functional properties of bee pollen produced in different locations

Abstract: This work aimed to investigate the physicochemical and functional composition of bee pollen produced in different municipalities in the state of Rio Grande do Norte/Brazil (RN) and commercial samples produced in other places. To perform these experiments, samples of dehydrated bee pollen were crushed and subjected to physicochemical evaluation, instrumental color, fatty acid profile, evaluation of the presence of bioactive compounds [Total Phenolic Compounds (TPC), carotenoids] and antioxidant activity (reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Based on the results obtained for carotenoid content, it can be concluded, in line with the literature, that PBP possessed a significantly higher content of carotenoids compared with a monofloral coconut sample from Brazil (2.17-3.55 µg/g dw) [31] or an artichoke bee-collected pollen sample from Serbia (5.00 µg/g dw) [26]. This difference may be related to the lighter color intensity observed in both coconut and artichoke bee-collected pollen samples [26,31] compared with that in PBP. Among the different phenolic subclasses, spectrophotometric analyses showed a significantly higher content for all phenolics in the extractable fraction compared with the bound fraction.…”
Section: General Phytochemical Compositionsupporting
confidence: 82%
See 3 more Smart Citations
“…Based on the results obtained for carotenoid content, it can be concluded, in line with the literature, that PBP possessed a significantly higher content of carotenoids compared with a monofloral coconut sample from Brazil (2.17-3.55 µg/g dw) [31] or an artichoke bee-collected pollen sample from Serbia (5.00 µg/g dw) [26]. This difference may be related to the lighter color intensity observed in both coconut and artichoke bee-collected pollen samples [26,31] compared with that in PBP. Among the different phenolic subclasses, spectrophotometric analyses showed a significantly higher content for all phenolics in the extractable fraction compared with the bound fraction.…”
Section: General Phytochemical Compositionsupporting
confidence: 82%
“…According to TPC results, the PBP extractable fraction contained a significantly higher amount of total phenolics compared with a sample with similar botanical origin-P. somniferum bee-collected pollen from Slovakia (0.82 mg/g GAE) [23]. However, the TPC result was in line with several beecollected pollen samples from Brazil [32], particularly with monofloral Mimosa caesalpiniifolia bee-collected pollen (12.1 mg/g GAE dw), while it was significantly higher compared with that of coconut (~2 mg/g GAE dw) [31], sunflower (extractable-2.9-3.8 GAE dw) [10] and artichoke (extractable-5.3 mg/kg GAE dw; bound-0.5 mg/g GAE dw) [26] monofloral bee-collected pollen samples from Brazil and Serbia, respectively. Moreover, a beecollected pollen sample from Morocco (Coriandum sativum + Cistaceae) showed a similar TPC value-13.73 mg/g GAE [33].…”
Section: General Phytochemical Compositionmentioning
confidence: 60%
See 2 more Smart Citations
“…Bee bread tested by the same authors showed pH values between 4.11 and 4.37 [13]. Similarly, pollen from different plants obtained from different regions of Brazil ranged from 4.55 to 5.09 [23]. The dependence of the pH decrease on the type of starter culture used for pollen fermentation was observed by Poyraz et al [24], and the largest decrease (from 5.13 to 4.15) was noted for the sample fermented with the fructophilic lactic acid bacteria (FLAB), Lactobacillus kunkeei, and the yeasts Starmeralla magnolia (MP-2) and Zygosaccharomyces siamensis (MP-14).…”
Section: Physicochemical Parametersmentioning
confidence: 79%